Peran Badan Penyelesaian Sengketa Konsumen (BPSK) dalam Penyelesaian Sengketa Konsumen (Studi Kasus : Putusan BPSK Badung No.01/AP/BPSK/IV/2016) - Arianto Hulu; A.A. Laksmi Sagung Dewi Ni; Made Sukaryati Karma (Warmadewa Press, 2020)
Indonesia, with the fourth largest population in the world, is a large market share for business actors. However, this potential is not free from negative things where business actors often only make consumers the object of their business activities without paying attention to the quality of the products being marketed so that consumers suffer losses. Responding to this phenomenon, the Consumer Dispute Resolution Agency (BPSK) was formed as an alternative means of dispute resolution between Buyers and Sellers with the aim of resolving disputes between the two parties in an effective and efficient non-litigation manner. This organization is not systemic but has the function of resolving conflicts that occur between producers and buyers on a non-litigation basis. This research was conducted with the aim of describing the forms of consumer legal protection for business actors and the role of BPSK in resolving consumer disputes. The research method used in this paper was a normative legal research method. This research showed that consumer legal protection for business actors is regulated in article 1 number 3 Law No. 8 of 1999 regarding consumer protection which states that a business actor is an entire person or individual or a business entity based on law or not and the place to carry out these activities in the territory of the Republic of Indonesia. In addition, BPSK has a role in carrying out the process and resolving consumer conflicts through mediation, arbitration or conciliation with opportunities ranging from consumer protection consultations, supervision in the application of agreements, making reports to investigators if there are indications of legal violations, receiving complaints, conducting studies and analysis of conflicts that occurred, summoning the parties, witnesses and any individual who is aware of an incident of law violation.